The effects of autocatalytic trade cycles on economic growth - Bakker, Jurriën J.; Afonso, Oscar; Silva, Sandra T. (Journal of Business Economics and Management, 2014)
This paper shows that autocatalytic trade cycles can be a positive feedback system for innovation and thus for economic growth. Using United Nations data, a trade network is proposed and a set of variables that represent the participation of countries in autocatalytic trade cycles is constructed. A clear relationship between these variables and economic growth is found since more innovation is produced in countries that are part of trade cycles. However, the relationship changes with autocatalytic trade cycle sizes, categories of goods and time scales. Moreover, autocatalytic trade cycles also have a positive effect for the trade flows involved, although this effect differs significantly depending on the size of the cycles. This new approach based on autocatalytic trade cycles emphasizes the benefits that countries can extract from trade cycles and points out the need of policies that foster these benefits. These conclusions strengthen existing literature, and also add new insights to innovation policy and the pursuit of economic prosperity.